MODEL PENDUGA BIOMASSA UNTUK TEGAKAN REHABILITASI DI HUTAN PENDIDIKAN GUNUNG WALAT (Jurnal ForestrIndo, 2024)
Forest rehabilitation plays an important role in increasing forest biomass and carbon stocks. However, there are limited studies that provide information on biomass growth of rehabilitates areas. This study aimed at developing stand biomass growth models for rehabilitated areas in Gunung Walat University Forest. The biomass data of Pinus merkusii stands were obtained by establishing and measuring 115 sample plots in various stand ages by applying the stratified systematic sampling method. The stand biomass growth models were developed by using regression analysis with independent variables consisting of age, diameter, height, basal area, and stand density. The results showed that the stand biomass of Pinus merkusii could be best estimated by stand age (A, year) and basal area (G, m2/ha) using the equation of W = 1,77A0,21G1,12 (R2adj = 99,27% and RMSE = 2,05 ton/ha). When the stand basal area data would not be available, the stand biomass could also be estimated using the equation of W = 0,06A-0,52D2,68 or W = 0,00057A2,37N1,25, which use the stand diameter (D, cm) and stand density (N, trees/ha) in addition to the stand age. These models are useful for the forest manager in estimating and monitoring the stand biomass growth of rehabiltated stands in Gunung Walat University Forest